Evaluating the Importance and Factors Affecting the Export Performance of Machine-Made Carpet Companies Based on Knowledge Domain Analysis and Fuzzy Network Analysis Model - Lajevardi , Seyed Reza; Ghodrati Ghazaani, Hassan; Panahian , Hossein; Arabzadeh , Meysam; Jabari , Hossein (AI and Tech in Behavioral and Social Sciences, 2025)
Although many of these insights address broader aspects of supply chain management and export competition among companies, such research lacks empirical evidence regarding the value acquisition of capabilities in companies under study concerning bargaining power and negotiation processes of companies active in the global value chain. Moreover, there is limited assessment of the impact of these factors on the export performance of manufacturing companies, particularly in the machine-made carpet industry. The present study aimed to evaluate the importance and factors influencing the export performance of machine-made carpet companies using knowledge domain analysis and the fuzzy network analysis model. The research methodology was theoretical-applied in terms of purpose, based on a survey research design and descriptive-inductive reasoning. Initially, key metrics affecting export performance were identified through knowledge domain analysis and qualitative content analysis. Subsequently, using a Delphi survey approach, 17 experts and specialists in the export field were selected through non-probability sampling. The fuzzy network multi-criteria analysis model was then employed to evaluate and refine the most effective metrics for measuring variables and to develop the proposed final model.